Best Answer

S = 3

st + 3t = 6

st = 6 - 3t

s = (6 - 3t)/t = 6/t - 3

Q: What is the answer for st plus 3t equals 6 solve for s?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

P=s r t , so, s= P/(st)

RT = 6 All you have to do is 15-9.

11

If triangle RST equals triangle MNO then RT = MO = 11 units. All the rest of the question - the lengths of RS and ST are irrelevant.

You need to write out the question before it can be answered.

Related questions

Unfortunately, limitations of the browser used by Answers.com means that we cannot see most symbols. It is therefore impossible to give a proper answer to your question. Please resubmit your question spelling out the symbols as "plus", "minus", "times", "divided by", "equals".

michael jackson

P=s r t , so, s= P/(st)

my name is Salvin if you want to see me come to st marks school

Ashley Stewart, in St. Louis, offers plus size clothing.

2mn - 2mt + 2sn - 2st = 0Divide both sides of the equation by 2:mn - mt + sn - st = 0m (n - t) +s (n - t) = 0(m + s) (n - t) = 0That's as far as you can go with the information given.

RT = 6 All you have to do is 15-9.

r = 3 s = 5 t = 6 rs = 3x5 = 15 rt = 3x6 = 18 st = 5x6 = 30

11

If triangle RST equals triangle MNO then RT = MO = 11 units. All the rest of the question - the lengths of RS and ST are irrelevant.

st+tut(s+u)

bc equals st multiplied by the scale factor.